Caries prevalence among children at public and private primary schools in Riyadh: a retrospective study - Budur Almutairi; Tasneem Rashed Adam; Rami Bustami (BMC, 2024)
Abstract Dental caries is a global oral health issue, especially critical in children, affecting their growth, nutrition, and education due to school absences or distractions from dental pain. The aim of the study was to investigate the correlation between school types (indicative of socioeconomic conditions) and dental caries prevalence among primary school children in Riyadh, alongside assessing the overall caries prevalence among schoolchildren in Riyadh. Retrospective study on 28,343 first and fourth-grade students from 960 public and private schools in Riyadh, using data from the Saudi Ministry of Health (Feb-April 2019). Utilized the DMFT/dmft index for assessment and collected demographic data. Most of the schools were public (76.1%), private national (17.1%), and private international (6.8%). Overall, the mean DMFT index for permanent teeth and the dmft index for primary teeth were 1.78 and 1.94, respectively. 58% of school children had no dental caries, 25% had mild caries, and 17% had moderate to severe caries. Public school children showed a higher caries prevalence than private schools. Oral disease rates were higher in girls than in boys, and grade four students had a higher prevalence than grade one students. Saudi Arabia, a developing nation, faces challenges in addressing oral health, especially in public schools. Targeted initiatives are crucial for awareness, preventive measures, and meeting oral health needs.